REPRESENTASI SEKSISME KORBAN KASUS PELECEHAN SEKSUAL ANAK PADA PEMBERITAAN MEDIA MASSA SIBER DI INDONESIA - Juwita, Silvia Ratna; Anshori, Dadang S.; Damaianti, Vismaia S.; Mulyati, Yeti (Master of Communication Science Program, Universitas Diponegoro, 2024)
The rise of cases of sexual violence against children in the world of education has become the focus of social cases that cannot be separated from cyber mass media coverage in Indonesia. Journalists occupy an important position because they represent information through the language they use to cover an event. Sexism is a form of language that risks being attached, especially in reporting on the marginalization of a gender. This study analyzes indirect sexism in cyber mass media with the highest readership in Indonesia using critical insight analysis from the Sara Mills approach and is a qualitative descriptive study. The results of this study found that the journalist's position in the news is a role in which the writer indirectly avoids perpetuating sexism by depicting the perpetrators of sexual assault. The indirect use of sexism by Indonesian online media journalists in reporting the case of sexual harassment of children/female students committed by an individual in charge of an Islamic boarding school in East Lombok is a form of representing the sexism exercised by the perpetrators against their victims. The indirect sexism employed by journalists shifts the focus of the news onto the victims of sexual harassment, ranging from the victims themselves to their families.